2019
DOI: 10.1186/s12882-019-1413-z
|View full text |Cite
|
Sign up to set email alerts
|

Mercury-associated glomerulonephritis: a retrospective study of 35 cases in a single Chinese center

Abstract: Background Long-term exposure of mercury may induce glomerulonephritis. Clinical and pathological features of mercury-associated glomerulonephritis are not fully clear. This study retrospectively analyzed 35 cases of mercury-associated glomerulonephritis in a single Chinese center. Methods Thirty-five patients of mercury-associated glomerulonephritis were enrolled. Clinical data on diagnosis and during follow-up were collected. Plasma anti-phospholipase A2 receptor (PLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…They also observed that in patients who received glucocorticoids or immunosuppression. 8 In our series, patients who received steroids had obtained an early remission despite having relatively higher urine and serum mercury levels. Mercury may persist in tissues despite normal serum and urine mercury levels.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…They also observed that in patients who received glucocorticoids or immunosuppression. 8 In our series, patients who received steroids had obtained an early remission despite having relatively higher urine and serum mercury levels. Mercury may persist in tissues despite normal serum and urine mercury levels.…”
Section: Discussionmentioning
confidence: 58%
“…reported their experience with combined immunosuppression and chelation with sodium dimercaptopropane sulfonate. 8 Those patients who received glucocorticoids and immunosuppression, along with chelation, had lower sodium dimercaptopropane sulfonate requirements. The median duration of remission with combined therapy was 2.5 months versus 4.5 months in patients who received chelation alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant level of As and Hg was reported with Mohammad et al, 2017 in skin bleaching agents of Caribbean region [50] As used in skin cream and make-up powder causes skin problems, lung cancer, circulatory and peripheral neuropathy, and increased risk of gastrointestinal and urinary tract malignancies [51,52]. Several recent and older studies reported nephrotic syndrome from repeated exposure of mercury and other heavy metals from skin lightening agent [53][54][55][56][57][58]. Dental amalgam has been used as a restorative treatment in dentistry for well over 170 years.…”
Section: Introductionmentioning
confidence: 97%